All the way to Havana - Engle, Margarita; Curato, Mike (New York : Godwin Books/ Henry Holt and Company, 2017)
A boy helps his father keep their very old car running as they make a trip to Havana for his newborn cousin's zero-year birthday. Includes author's note about cars in Cuba.
Keywords: Automobile travel -- Fiction; Automobiles -- Maintenance and repair -- Fiction; Family life -- Cuba -- Fiction; Automobile travel -- Juvenile fiction; Automobiles -- Maintenance and repair -- Juvenile fiction; Families -- Cuba -- Juvenile fiction; Family life -- Cuba -- Fiction; Automobile travel -- Fiction; Automobiles -- Maintenance and repair -- Fiction